If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 13 + -6x = -8 + 12 Reorder the terms: 13 + 7x + -6x = -8 + 12 Combine like terms: 7x + -6x = 1x 13 + 1x = -8 + 12 Combine like terms: -8 + 12 = 4 13 + 1x = 4 Solving 13 + 1x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 1x = 4 + -13 Combine like terms: 13 + -13 = 0 0 + 1x = 4 + -13 1x = 4 + -13 Combine like terms: 4 + -13 = -9 1x = -9 Divide each side by '1'. x = -9 Simplifying x = -9
| 5+6h=6+2h | | 3(5+7x)=-132 | | 5+6h=6 | | 2y=4(0)+5 | | 4x+5(6x-18)=148 | | 2y=2(0)+1 | | 7x+2(x+15)=84 | | 23x+15=8x | | 8x+7-3x=-6x-15+x | | 2x+7(3x-4)=179 | | 3y+2x=62 | | x^2+5-(7+3*x)= | | 2.3*(-1.2)= | | 7-7x=34-14x | | -35+8+m=-8+11 | | 6x+2(4x+15)=198 | | -1.1*(-8)= | | -15*(-3)= | | 0.4n+-18=3n-16-0.8n | | 5x+5(2x+18)=195 | | 6x+10=-48-8x | | y+31=-55 | | 16-m^2=0 | | w^2+8w+48=0 | | 2[(3)+2]4= | | 0.4n-18=3n-16-0.9n | | a^2-10-3a= | | 6(2x-5)-3(x+2)-18x= | | 2(6-2b)=0 | | 2(3m-10)= | | 5y+2=3y-1 | | 2(3m+5)= |